Optical doping of ZnO with Tm by ion implantation - Rita, E.
ZnO [0 0 0 1] single-crystals were implanted at room temperature with 150 keVTm+ ions at a fluence of 5 × 1015cm -2. Each sample was then subjected to one single 30min air annealing at 800°C, 950°C and 1050°C. The Tm lattice site location and defect recovery were investigated with Rutherford Backscattering/Channeling Spectroscopy. Detailed angular scans along the [0 0 0 1] direction show that 94% of the Tm ions occupy substitutional Zn sites (SZn) in the as-implanted sample. All the annealing temperatures lead to a reduction of this fraction to 30%. Also, progressive damage recovery and Tm segregation to the surface were observed, being enhanced at 1050°C. Photoluminescence (PL) studies with above band gap excitation performed on these samples revealed no luminescence on the as-implanted state. The 800°C air annealing promotes the Tm3+ optical activation and a well-defined near-infrared intraionic emission is observed. For higher annealing temperatures, in spite of no change of the Tm fraction at SZn sites, a decrease of the Tm intraionic emission was observed. These results suggest that optical activation of Tm ions is related with the defect density in their environment. © 2003 Elsevier B.V. All rights reserved.